The Abundance of Gastropods in the Mangrove Ecosystem of Kuala Langsa, Langsa Barat Districts, Langsa City - Cut Rushayu Putri; M. Ali S; Mimie Saputri; Ismul Huda; Abdullah Abdullah (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2021)
Gastropods are a class of the Phylum Mollusca, which use their stomachs as legs for walking. Gastropod habitat at this time, disturbances occur due to the many activities and changes in environmental physico-chemical factors are feared to cause a decrease in the number and abundance of gastropod species. This study aims to assess the abundance of Gastropods. The study was conducted from August to September 2020 in the Kuala Langsa Mangrove Ecosystem Area, West Langsa District, Langsa City. The research method used is a survey method with purposive sampling technique, consisting of 4 stations with 3 sampling times. Analysis of the abundance level was calculated using the formula for abundance and relative abundance. The results showed that the abundance of species of Gastropods amounted to 422.50 Ind/m2 and the relative abundance values ranged from 1% to 35%, indicating that the abundance levels were low and high.Keywords: Abundance,  Gastropods,  Mangrove Ecosystem, and Kuala Langsa